The mitochondrial DNA control region sequences from the Chinese Miao population of southeastern China - Cuiyun Le; Zheng Ren; Hongling Zhang; Qiyan Wang; Meiqing Yang; Yubo Liu; Jiang Huang; Jie Wang (Taylor & Francis Group, 2019)
Background: Miao people are an officially recognised ethnic group living in southwest China, but have seldom been studied genetically, especially with respect to mtDNA data. Aim: To investigate the sequences and haplogroups of the mtDNA control region in a typical Miao population, with the aim of providing a good start for the expansion of the East Asian mtDNA reference database for forensic DNA analysis. Subjects and methods: We analysed 203 Miao individuals, looking at mtDNA control region sequences. We calculated and illustrated the haplotype frequencies, haplogroup distribution and pairwise Fst values between the Miao and six other worldwide populations to explore genetic polymorphisms and population relationships. Results: We observed 121 haplotypes with corresponding frequencies ranging from 0.0049 to 0.0690 in the Miao population. All the samples were assigned to 71 different haplogroups. The haplotype diversity and the random match probability were estimated to be 0.9844 and 0.0204, respectively. The pairwise Fst values and associated p values among seven populations suggest that the Miao population has significant differences to the other six populations, and is relatively isolated compared with them. Conclusions: Our results suggest that frequency estimates for mtDNA haplotypes in Miao ethnic groups should be determined independently rather than being pooled with other populations.